Unraveling hydraulically fractured shale-microbe interaction for biogenic methane enhancement - Ganeson, M. (European Association of Geoscientists and Engineers, EAGE, 2021)
Research in shale-microbe interaction has gained profound attention at the current time frame due to advanced horizontal drilling and hydraulic fracturing process in unconventional reservoirs. Since the hydraulic fracturing has altered and changed the biogeochemical conditions in shale ecosystem, this paper aimed to provide an overview of possible microbial metabolism (methanogenesis) in the context of enhancing biogenic methane gas. Some of the key points are described as below: â¢ Hydraulic fracturing provides physical space, nutrients and allowed enrichment of microorganisms in fluids during natural gas production. â¢ Input chemistry (fracking additives) and adaptation to salinity drives a methylamine and acetolastic food-web that results in biogenic methane production. â¢ Shale is a source of salinity that selects for organisms that produce osmoprotectants like glycine-betaine. This substrate can be fermented by the consortium of microbial community to yield sustainable methanogenic substrates. Thus, the information provided here would able to give a sufficient overview of methanogenesis in hydraulic fractured shale and may enable the microbiologist, geologist and engineers to work in a collaborative manner to explore the possibility of advancing biogenic methane as future energy technology. Â© EAGE Asia Pacific Virtual Geoscience Week 2021. All rights reserved.